Mudanças Espaciais na Casa Republicana. A Higiene Pública e Outras Novidades - Homem, Maria Cecília Naclério (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1993)
In the beginning of the century, the recently proclaimed Republic (1889) proposed a new political program, based preferably on public hygiene. It took the control of the domestic and urban space by means of a strict legislation and the execution of works related to the sanitation of land and water. The urban dwelling had difficulties in fitting the new utilizations on the whole it remained dependent on popular plots of land — narrow and elongated — as well as on the street alignment. Inside it also preferred the traditional distribution, displayed in the front-backyard direction. The rich and large dwellings, having bigger plots of land, introduced spontaneously resources to comply with the hygiene propositions, such as drawing back the boundaries of the plot and displaying a new distribuition